Lightning Death: A Case Report - Sumangala , C N; Pradeep , Kumar MP (Journal of Indian Academy of Forensic Medicine, 2015)
Death due to lightning is a rare phenomenon in day to day autopsy. Even though, fatalities due to  lightning are more in rainy, hilly areas, such cases are rarely encountered in and around Bangalore.  Lightning is mostly associated with rain and many a times electrocution are also commonly seen which  has to be differentiated from injuries due to lightning. Adults and elderly are people involved in lightning  related injuries and many are non fatal but, if children are involved it may lead to a fatal consequence.  Such parameters are to be studied in cases of fatal lightning death in both adults and children. Lightning  fatalities are rarely read in literature in medical science and lot needs to be studied in this view as many  bread earners are involved in such fatalities. In a country like India where the climate is of both tropical  and subtropical type study about lightning deaths needs more emphasis in aspects of both treatment and  prevention of human fatalities. Here, one such fatal case of lightning of a child is reported, though  uncommon in children than in adults.
Keywords: Lightning; Injury; Death; Electrocution; Fatalities